Double link sensor for mitigating tilt- horizontal coupling. (1st April 2022) - G Nair, V.; Collette, C.
Abstract: The sensitivity of inertial sensors, intended for horizontal motion detection, to tilt due to gravity at low frequency is known as tilt horizontal coupling. This is crucial for numerous seismological studies and seismic isolation applications such as gravitational wave detection. This paper presents a new sensor architecture for mitigating tilt horizontal coupling when exposed to pure translation or tilt. The proposed Double Link (DL) sensor does not need any additional mechanisms and is only sensitive to the translation and negligibly sensitive to tilt. The sensor is in the form of a double pendulum hanging from a platform and the measured output is the relative motion between the two links. The simulations are carried out in Simscape environment and the results confirms the efficiency of the system. The study was carried out as a part of the ETEST project which is aimed at developing a prototype for the future Einstein Telescope Gravitational Wave detector.